Educação matemática e Educação de Jovens e Adultos: estado da arte de publicações em periódicos (2000 a 2010) - Freitas, Adriano Vargas (2013)
This thesis is part of the work developed within the research group "Curriculum Development in Mathematics and Teacher Education" and the Research Project "The mathematics curriculum in the Education of Youth and Adults (EJA)" PUC-SP. This research aims at investigating the productions that present scientific contributions in the area of mathematics education area for understanding and advances in EJA. The study was developed on the model of state of the art, providing analysis of journals publications including the Qualis MEC listing, in the Teaching of Science and Mathematics, related to Mathematics Education for Adult Education, published from 2000 to 2010. The production analysis allowed the establishment of four themes, which enabled us to answer the following questions: a) What was produced and published on Training / Practice Teacher / EJA Literacy? b) What was produced and published on Pedagogical Practices in Adult Education? c) What was produced and published on EJA Curriculum? d) What was produced and published on EJA Evaluating? Among the main results, we highlight: convergence to the indication of a more investigative attitude, by the teacher on oral and written work of their students, encouraging them to report their prior knowledge and compare them critically to the one developed during the lessons; adoption of greater flexibility in standardization requirement in the expression of mathematical procedures, interpreting errors as manifestations of the restructuring process and not anymore as personal failures or shortcomings; legal defense that in EJA we should not adopt a previous prescription curriculum, disregarding the specificities of their students and their different learning processes and progress